Framingham Risk Score and Coronary Artery Calcium Score: How Good they Relate - Johanes Nugroho; Revi Adheriyani; Ardyan Wardhana; Makhyan Jibril Al Farabi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background and Aims: Screening patients for coronary arterial disease can be through risk stratification using theFramingham Risk Score (FRS). Direct visualization of subclinical atherosclerotic lesions through coronary arterycalcium scores (CACS) can be an additional strategy. Therefore, we want to know the relationship between FRSand CACS in asymptomatic individuals.Method: A cross-sectional study involving 110 asymptomatic participants who undergoing health screening wasconducted in the National Hospital, Surabaya from November 2015 until January 2016. Risk stratification wasevaluated using Hard Coronary Heart Disease (10-year risk) outcomes model score and the Agatston–Janowitz’scoronary calcium score.Results: A significant positive correlation was observed between CACS and FRS (Spearman’s correlation coefficientr=0.51, P<0.0001). Age and systolic blood pressure were also positively correlated with CACS. Total cholesterolwas the only parameter that showed a negative correlation with CACS. No difference in CACS value was shownin gender and smoking status.Conclusion: There was a strong correlation between FRS and CACS in asymptomatic individuals.